The Possibility of Applying Agile Internal Auditing in the Iraqi Economic Units - Halim Mohamed Amin, Hind; Adnan Noman Al-Shammari, Suad (Journal of Economics and Administrative Sciences, 2023)
The research problem is that the traditional methods of internal auditing are somewhat heavy with long and rigid procedures for the members of the audit process team, especially in light of the current developments that are reflected in the business environment and internal audit reports, so it is necessary to reconsider the traditional internal audit work method and assess the extent of its development by agile methods to reduce the time of the audit process on the activities and elements that add value and direct the effort and time to the activities and elements that add value to the work of the economic unit and the report of the internal auditor.The research aims to study the possibility of applying agile internal auditing in the Iraqi economic units and to achieve the goal of the research. The researchers made a checklist to test the research hypothesis, which states (there are no applications of lean internal auditing methods in the local environment). For (6) private banks listed in the Iraq Stock Exchange, which number (69) banks, after reviewing the periodic reports prepared by the Central Bank of Iraq.The researchers concluded that the banks of the research sample applied to the graceful internal audit in the Iraqi economic units is the Ashur Bank, as it obtained the highest arithmetic mean reached (2.55) and the highest relative importance as it amounted to (85.0%) and the second place the Iraqi Investment Bank got the arithmetic mean (2.48) and importance Relative (82.7%). In third place, the Khaleej Commercial Bank got an arithmetic mean (2.39) and relative importance (79.7%). In fourth place, the Trans-Iraq Bank got an arithmetic mean (2.28) and relative importance (76%). In fifth place, the Iraqi Islamic Bank got on the arithmetic mean (2.24) and relative importance (74.7%). Paper type: Research Paper